PENGARUH KESADARAN WAJIB PAJAK DAN SANKSI PAJAK KENDARAAN BERMOTOR TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR: KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - Andhea Puspita; Siti Asmonah (Yayasan Kayyis Mulia Jaya, 2025)
This study aims to: (1) determine and analyze the effect of taxpayer awareness on the compliance of motor vehicle taxpayers in Tangerang Regency; (2) determine and analyze the effect of tax sanctions on the compliance of motor vehicle taxpayers in Tangerang Regency; and (3) determine and analyze the simultaneous effect of taxpayer awareness and tax sanctions on the compliance of motor vehicle taxpayers in Tangerang Regency. The method used is a quantitative approach with multiple linear regression analysis. Data were collected through questionnaires distributed to 100 respondents registered at the UPTD PPD Samsat Kelapa Dua. The results show that taxpayer awareness has a positive and significant effect on compliance, with a t-value of 9.628 and a significance level of < 0.001. On the other hand, tax sanctions do not have a significant partial effect, with a t-value of 1.420 and a significance level of 0.159. However, simultaneously, taxpayer awareness and tax sanctions significantly affect taxpayer compliance, as indicated by an F-value of 140.482 and a significance level of < 0.001. The coefficient of determination (R²) is 0.738, indicating that 73.8% of the variation in compliance can be explained by these two variables. These findings affirm that taxpayer awareness is the dominant factor in driving compliance, while the effectiveness of tax sanctions depends on consistent implementation and regional policies such as tax amnesty programs. This study contributes to local governments in designing more effective education and law enforcement strategies to enhance regional tax revenue. Keywords: Taxpayer Awareness, Tax Sanctions, Tax Compliance, Motor Vehicle Tax.